Examining Masculinities and Femininity in Tennessee William’s A Streetcar Named Desire - Manjari Johri (Pusat Studi Gender Universitas Jember, 2024)
Examining A Streetcar Named Desire through the lens of Gender and Masculinity Studies is an academically enriching and intriguing pursuit. The play, first performed on Broadway in 1947, continues to captivate with its portrayal of the characters of Stanley and Blanche. Stanley’s aggressive masculinity is pitted against the frailty of Blanche, leading to her breakdown and her ultimate escape into the unreal world of fantasy. This study aims to identify different types of masculinities; from Allan Grey’s closeted identity to Stanley Kowalsky's toxic masculinity, and how each affects Blanche Du Bois. It is intriguing to explore whether her distraught emotional state is entirely due to Stanley’s bestial toxicity or whether she is also a victim of femininity which is synonymous with frailty, beauty, and obsession with eternal youth. R.W. Connell’s Masculinities (1995,2005), and Betty Friedan’s The Feminine Mystique (1963) have been used as a framework to evaluate the male and female characters in the play.